Evaluation of Pulsed Electric Field Polyphenol Extraction from Vitis vinifera, Sideritis scardica and Crocus sativus - Achillia Lakka; Eleni Bozinou; Dimitris P. Makris; Stavros I. Lalas (ChemEngineering, 2021)
This study exploited the application of pulsed electric field (PEF) on the recovery of polyphenols from aerial parts of Sideritis scardica, tepals of Crocus sativus, and fruits of Vitis vinifera. Short pulses of 10 μs in a period of 1 ms were applied to the plant material, while different electric field intensities, 1.2 to 2.0 kV/cm were tested to optimize the procedure. The content in total polyphenols and the polyphenolic profile of the plant extracts were evaluated. Along with PEF samples, control samples were prepared for comparison. PEF treatment enhanced the recovery in total polyphenols for all the three plants examined. A significant increase was noticed in each plant tested and PEF condition applied, though lower electric field intensities up to 1.4 kV/cm proved to be more effective. Under the optimum electric field intensities, 1.4 kV/cm for V. vinifera and 1.2 kV/cm for S. scardica and C. sativus, increases of 49.15%, 35.25%, and 44.36% in total polyphenol content, respectively, were achieved. Additionally, an 85% increase of quercetin 3-rutinoside for V. vinifera, a 56% of apigenin 7-O-glucoside for S. scardica, and a 64% increase for kaempferol 3-O-glucoside for C. sativus were obtained.